Case report of ulcerative pyoderma gangrenosum of the forearm: A challenging diagnosis (Indian Journal of Case Reports, 2020)
Pyoderma gangrenosum (PG) is an uncommon disease associated with significant morbidity, characterized by the rapid development of a painful, necrolytic ulcer with undermined, irregular margins. Various clinical or histological subtypes have been illustrated in the literature. The diagnoses of various subtypes of PG are difficult due to its uneven presentation, clinical overlap with other conditions and not have specific diagnostic laboratory tests or classical histopathological findings. PG is frequently misdiagnosed as infection, results in delay or inappropriate treatment of the same, which leads to devastating results such as amputation of limbs and even demise. We report here the rare case of a 64-year-old woman who had initially presented with tender papules over the right forearm, later developed expanding ulcers and underwent serial debridements, which resulted in extensive ulcerative PG at the same site. This case highlights the challenges being faced while diagnosing ulcerative PG, emphasizes the key clinical and histopathological findings to aid in the final diagnosis, and also the clinical consequences of delayed diagnosis of this condition.